Sosialisasi Protokol Kesehatan di Masa New Normal Bagi Nelayan - Ismail Ismail; Endang Gunaisah; Hendra Poltak; Serisanthi Irsani Oklan Bothmir (Politeknik Kelautan dan Perikanan Sorong, 2021)
Covid-19 has invaded almost all regions and professions, including coastal areas which are mostly inhabited by fishermen. Solidarity with fishermen during a pandemic is carried out by socializing health protocols to prevent the Covid-19 pandemic from spreading to fishermen. There were 30 socialization participants who were handline fishermen from three groups of fishermen in Maladum Mes District. Evaluation of the results of socialization by making observations in the fishing area found that on average fishermen do not use masks for various reasons. However, fishermen have behaved to keep their distance.